Band gap closure, incommensurability and molecular dissociation of dense chlorine - Philip Dalladay-Simpson; Jack Binns; Miriam Peña-Alvarez; Mary-Ellen Donnelly; Eran Greenberg; Vitali Prakapenka; Xiao-Jia Chen; Eugene Gregoryanz; Ross T. Howie (Nature Communications, 2019)
Molecular systems are predicted to transform into atomic solids and be metallic at high pressure; this was observed for the diatomic elements iodine and bromine. Here the authors access the higher pressures needed to observe the dissociation in chlorine, through an incommensurate phase, and provide evidence for metallization.